Desarrollo de una guía multimedia para la asignatura de lengua de señas como apoyo para el proceso de aprendizaje de los estudiantes de cuarto año de educación general básica de la Unidad Educativa Especializada Sordos de Chimborazo. - Orden Guamán, Carlos Raúl (2016)
This research aims to implement a multimedia guide to enhance the vocabulary on the subject of sign language in the Special Educative Unit Deaf of Chimborazo, where it was observed that the lack of technological training materials of this subject brings in students loss of interest in learning. While the teacher uses the traditional method of learning, where their classes taught are through printed materials, resulting on failing to meet the required competencies. The type of research used is applied and technology because it develops the technological and computer product embodied through a multimedia guide. For the development of this program was chosen the methodology Development of Educational Software (DESED), which allowed the development of software in an organized way in the phases : Planning, Analysis, Design, Implementation, Testing and product launch, the same allowing the guide to meet the needs required by students for learning. An evaluation was performed using the methodology Assessment of Educational Software Zulma Cataldi, resulting in a 93% satisfaction, concluding that the use of educational applications is very important for both the teacher and the student, innovates the learning process and also motivates students to learn.